"LANDSCAPE PLOTTED AND PIECED": EXPLORING THE CONTOURS OF ENGAGEMENT BETWEEN (NEURO)SCIENCE AND THEOLOGY: with Pat Bennett, "'Landscape Plotted and Pieced': Exploring the Contours of Engagement between (Neuro)science and Theology"; Pat Bennett, "'Things Counter, Original, Spare, Strange': Developing a Postfoundational Transversal Model for Science/Religion Dialogue"; and Pat Bennett, "'Áll Trádes, Their Gear and Tackle and Trim': Theology, Cognitive Neuroscience, and Psychoneuroimmunology in Transversal Dialogue.". Issue 1 (17th February 2019) - Bennett, Pat
Abstract: This article—the first of a linked set of three outlining the development and practice of a different approach to science/religion dialogue—begins with an overview of some persistent tensions in the field. Then, using a threefold heuristic of encounter, engagement, and expression, it explores the routes taken by James Ashbrook and Andrew Newberg to develop a dialogue between theology and neuroscience, discussing some of the problems associated with these and their implications for attempts to further develop neurotheology. Finally, it proposes a different way of thinking about this enterprise and points toward a new methodology for supporting this endeavor.